Effect of the inclination of support in cervical and upper limb development - Ailime Perito Feiber Heck; Micheli Martinello; Daiane Lazzeri de Medeiros; Jerusa Jordão Coelho; Lilian Gerdi Kittel Ries
Introduction It is expected that a child will acquire control of posture (CP) of the head and upper limbs in a gradual, sequential and organized way. However, there is still no consensus regarding the best position to achieve this; the evidence suggests that it is prone. Objective To investigate whether age and inclination of the supporting surface in the prone position influence the alignment of the head and upper limbs of children with typical motor development (TMD) and atypical motor development (AMD). Methods The study included 29 children aged between one and three months divided according to the Alberta Infant Motor Scale (AIMS) into groups with TMD (n = 18) and AMD (n = 11). The children were placed in the prone position with three angles of the support surface (0°, 25° and 45°). Kinematic analysis was conducted to evaluate the alignment angles of the head and upper limbs. Results Children with TMD had higher head alignment. There was no difference in the upper limbs' alignment between the group with TMD and the group with AMD. In the third month of age compared with the first, increased head alignment and decreased upper limb alignment were found in both groups. The inclination of the supporting surface did not influence the alignment of the head and upper limbs. Conclusions Among the positions evaluated, the prone position without inclination of the supporting surface was more appropriate for weight discharge in the upper limbs, favoring the development of postural control of the child.